Manajemen Pendistribusian Zakat di Masa Pandemi Covid-19 - Moh Khoirul Anam; Irpan Hardiansah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Zakat collection has great potential and is channelled effectively, zakat can contribute to national development, especially in poverty alleviation. The arrival of the covid 19 pandemic invites the active role of zakat institutions to help people who are hampering the pandemic. Zakat institutions also face limitations in management because they also have to carry out operations with Health protocols. Zakat institutions develop creativity in maximizing the collection and distribution of zakat funds. Looking at the phenomenon of research on the role of zakat institutions and the operational constraints faced to examine this phenomenon, delivering zakat funds during the covid 19 pandemic. The research was carried out in Lazismu Kota Depo. The study was conducted in early 2021 to see the activities of distributing zakat funds at the beginning of the covid 19 pandemic in 2020. The results showed that during the covid 19 pandemic the distribution of ZIS funds in Lazismu Kota Depok went well. Management applies the concept of management science which consists of the planning process to evaluation. This strategy is quite effective in dealing with existing obstacles. For example, operational constraints due to the Health protocol and the lack of special program staff to implement the ZIS fund distribution program.